Status Hukum Perkawinan terhadap Salah Satu Pasangan yang Telah Murtad - Manik, Irvan Juli Alfredo; Rodliyah, Nunung; Adhan S, Sepriyadi (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Marriage in Indonesia is governed by a dual legal system religious law and national law which often intersect in cases involving religious conversion (apostasy) after marriage. This study investigates the legal status and consequences of marriage when one spouse becomes an apostate. The research uses an applied normative legal approach, relying on secondary data including primary legal sources, scholarly literature, and legal interpretations. Data were collected through document studies and interviews and analyzed qualitatively. The findings reveal that under Law Number 1 of 1974 concerning Marriage, the marital bond remains legally valid until a court decision declares a divorce. However, the Compilation of Islamic Law (KHI) stipulates that apostasy by either spouse automatically invalidates the marriage. As a result, the couple loses mutual inheritance rights and is prohibited from engaging in marital relations until a divorce is formalized. This study highlights the legal ambiguity and dualism faced by Indonesian couples in inter-religious contexts and calls for clearer legal reconciliation between Islamic jurisprudence and national marriage laws to ensure legal certainty and protect family rights.